A note on higher rank descriptions of massless and massive spin-1 particles - Dalmazi, D. [UNESP]; Barbosa, F. A. da Silva [UNESP]; Santos, A. . L. R. dos [UNESP] (Elsevier B.V., 2022)
The Maxwell theory can be written as a first order model with the help of a two-form auxiliary field, such master action allows the proof of duality between 1-form and D - 3 forms. Here we show that the replacement of the two-form auxiliary field by an arbitrary (non symmetric) rank-2 tensor leads to a new massless spin-1 dual theory in terms of a partially antisymmetric rank3 tensor. In the massive spin-1 case we have a non symmetric generalization of the massive two-form theory (Kalb-Ramond). The coupling of the massive non symmetric spin-1 model to matter fields is investigated via master actions. We also show that massive models with severe discontinuity in their massless limit can also be obtained from Kaluza-Klein dimensional reduction of massless higher rank tensors which become Stueckelberg fields after the reduction. (c) 2022 Elsevier Inc. All rights reserved.
Keywords: Proca theory; Spin-1; Higher rank; Dual model; Dimensional reduction